Workload Analysis on CV Saswco Perdana - Mayasari, Mia; Gustomo, Aurik (Journal of Business and Management, 2014)
The research aimed to find out how the workload can be evenly distributed in CV.SaswcoPerdana, so employees have clear job analysis. The methodology used is Workload Analysis. Primary data is collected by questionnaires and workload form that distributed to 12 employee and interview the management. There are several job positions are overload and under load. Overall, the most employees understand their job analysis and know their standard workload. Suggestions for CV.Saswco Perdana are company should review the job description for employee of each position and reduce some overload job to under load job. Keywords: Workload, Job Description, Human Resources Management, Workload Analysis Category: Human Resources Management, Human Resources Planning, Work System, Workload Analysis